The last garden in england ebook - Kelly, Julia (2021)
From the author of the international bestsellers The Light Over London and The Whispers of War comes "a compelling read, filled with lovable characters and an alluring twist of fates" (Ellen Keith, author of The Dutch Wife ) about five women living across three different times whose lives are all connected by one very special garden. Present day: Emma Lovett, who has dedicated her career to breathing new life into long-neglected gardens, has just been given the opportunity of a lifetime: to restore the gardens of the famed Highbury House estate, designed in 1907 by her hero Venetia Smith. But as Emma dives deeper into the gardens' past, she begins to uncover secrets that have long lain hidden. 1907: A talented artist with a growing reputation for her work, Venetia Smith has carved out a niche for herself as a garden designer to industrialists, solicitors, and bankers looking to show off their wealth with sumptuous country houses. When she is hired to design the gardens of Highbury House, she is determined to make them a triumph, but the gardens—and the people she meets—promise to change her life forever. 1944: When land girl Beth Pedley arrives at a farm on the outskirts of the village of Highbury, all she wants is to find a place she can call home. Cook Stella Adderton, on the other hand, is desperate to leave Highbury House to pursue her own dreams. And widow Diana Symonds, the mistress of the grand house, is anxiously trying to cling to her pre-war life now that her home has been requisitioned and transformed into a convalescent hospital for wounded soldiers. But when war threatens Highbury House's treasured gardens, these three very different women are drawn together by a secret that will last for decades. "Gorgeously written and rooted in meticulous period detail, this novel is vibrant as it is stirring. Fans of historical fiction will fall in love with The Last Garden in England " (Roxanne Veletzos, author of The Girl They Left Behind ).